An intense precipitation event causes a temperate forested drainage network to shift from N2O source to sink. Issue Volume 67:Issue S1(2022)Special issue (13th January 2022) - Aho, Kelly S.; Fair, Jennifer H.; Hosen, Jake D.; Kyzivat, Ethan D.; Logozzo, Laura A.; Weber, Lisa C.; Yoon, Byungman; Zarnetske, Jay P.; Raymond, Peter A.
Abstract: Nitrous oxide (N2 O) evasion from streams and rivers is a significant, yet highly uncertain, flux in nitrogen cycle models. Most global estimates of lotic N2 O emission assume that evasion rates are proportional to inorganic nitrogen inputs to a stream or river. However, many field studies do not detect relationships between lotic N2 O evasion and dissolved nitrogen concentration, highlighting the need for better understanding of process‐based controls on this flux. This study reports 4‐yr time series of p N2 O and N2 O evasion from eight nested streams and rivers and detects an abrupt change in N2 O dynamics associated with an intense rainstorm. This rainstorm, and the associated hydrologic flood event, pushed forested reaches across the watershed from consistent N2 O sources to prolonged N2 O sinks. We attribute this shift to disturbance of incomplete denitrification in the stream network and surrounding watershed, although alternate hypotheses are also discussed. There was continued availability of nitrate ( NO 3 − ) for in‐stream processing, eliminating the possibility that NO 3 − ‐availability limited N2 O production, and post‐storm N2 O‐to‐nitrate ratios were lower than pre‐storm ratios suggesting that the large storm affected in‐situ nitrogen processing rates. The sustained period of post‐storm N2 O undersaturation resulted in net negative evasion for five of the eight study sites in 2018, which mitigated emissions over the 4‐yr study. This nonlinear response in N2 O dynamics illustrates the potential importance of storm events to control lotic N2 O production and emissions.